CERIA English Learning: A Creative Program to Boost Motivation of SDN Puton Jombang Students - Iin Noviana; Shanti Rosmaharani; Rodiyah; Syaputra Dwi Santoso (Jurnal Dremi (Demi Pengabdi Masyarakat), 2025)
The CERIA English Learning programme at SDN Puton Jombang was implemented to address low motivation, limited participation, and low self-confidence among primary school pupils in learning English in a rural school context. The programme aimed to create an enjoyable, low-anxiety learning environment through a combination of English songs, gamified classroom activities, and low-cost interactive media, including basic augmented reality. Activities were conducted on 15 and 16 May 2025 with 70 pupils from Years 4 to 6, structured into preliminary, core, and closing sessions. The impact of the programme was evaluated using a pre–post motivation scale, classroom observation sheets, and participant satisfaction ratings. The results showed increases in mean scores for motivation, confidence in speaking, active participation, and mastery of basic English vocabulary, with gains ranging from 25.0% to 32.0%. Satisfaction ratings from pupils and teachers for the content, methods, facilitators, and media were in the “very satisfied” category, while visual documentation indicated a livelier and more collaborative classroom atmosphere. These findings suggest that CERIA is an effective and realistic model of creative English learning for resource-constrained primary schools and has potential to be strengthened through teacher training and replicated in other settings.